The influence of product quality, promotion, and digital marketing on purchasing decisions through consumer satisfaction as a mediating variable - Anjalita, Lara; Suhardi, Suhardi (Economic: Journal Economic and Business, 2026)
This study aims to analyze the influence of product quality, promotion, and digital marketing on purchasing decisions with consumer satisfaction as a mediating variable among TikTok Shop users among Generation Z. This study uses a quantitative approach with Partial Least Squares–Structural Equation Modeling (PLS-SEM) analysis techniques. The results show that product quality and promotion do not have a direct and significant effect on purchasing decisions, but both have a significant indirect effect through consumer satisfaction. Meanwhile, digital marketing has a direct and indirect effect on purchasing decisions. Consumer satisfaction is proven to play a significant role in bridging the relationship between independent variables and purchasing decisions. These findings emphasize the importance of digital marketing strategies that focus not only on product presentation or promotion, but also on improving consumer experience and satisfaction to encourage purchase conversions, especially in the Generation Z segment that is highly responsive to digital experiences. This study provides practical implications for business actors to prioritize building consumer satisfaction in improving purchasing decisions through optimizing product quality, promotional strategies, and utilizing targeted digital marketing.